The Predictive Power of Oil and Commodity Prices for Equity Markets - Dagher, Leila (2018)
Using a seven-variable Vector Autoregressive (VAR) model and a rolling window approach, this paper investigates causality between oil price changes and the aggregate stock market returns of France, Italy, Saudi Arabia and the United Arab Emirates. We provide strong empirical evidence that oil price changes cause aggregate stock returns for the two oil-exporting Arab countries starting in 2014. Since the post-2014 period is one of declining oil prices, our findings may suggest that causality depends on the prevailing oil price regime. Our findings also suggest that copper price changes are, to a lesser extent, useful predictors of the equity returns of Saudi Arabia and the United Arab Emirates.